1988
DOI: 10.1002/ajh.2830270303
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in chronic myelodysplastic syndromes: A multivariate analysis in 107 cases

Abstract: A retrospective multivariate analysis of 37 clinical, biochemical, and hematological data was performed in 107 cases of primary myelodysplastic syndromes (MDS) in order to recognize their prognostic significance. The most important individual variables, isolated in a previous univariate analysis, were placed in a multiple regression modeling procedure to identify major significant prognostic factors. Multivariate analysis tends to identify prognostic variables containing significant independent predictive info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 11 publications
0
9
0
3
Order By: Relevance
“…Dysplastic features were quantified using the score system devised by the Spanish Cooperative Group for the Study of Myelodysplastic Syndromes 16,17 as shown in Table 1. It assigns values depending on the grade of dyserythro-, dysgranulo-and dysthrombopoiesis.…”
Section: Morphological Studiesmentioning
confidence: 99%
“…Dysplastic features were quantified using the score system devised by the Spanish Cooperative Group for the Study of Myelodysplastic Syndromes 16,17 as shown in Table 1. It assigns values depending on the grade of dyserythro-, dysgranulo-and dysthrombopoiesis.…”
Section: Morphological Studiesmentioning
confidence: 99%
“…El síndrome hemorrágico fue el segundo en frecuencia de presentación en los pacientes con un 28%, igual al 28.3% que reporta Giralt (10) en su estudio, pero ligeramente superior al 24% encontrando por Fourcar (11) y al 20% de Sanz (9). En cuanto al síndrome infeccioso lo encontramos en un 17% de los pacientes, porcentaje que está entre 10 a 20% descrito en la literatura (10,12).…”
Section: Discusionunclassified
“…Encontramos 8 pacientes con AR, dos con ARSA, tres con AREB, uno con LMMC y cuatro con AREBt. Varios estudios han demostrado relación entre la variedad y el tiempo de sobreviva (9,12,25,26), teniendo mejor pronóstico ARSA luego AR, LMMC y con el peor pronóstico AREBt. Nosotros no hemos podido calcular el tiempo de sobrevida separadamente para cada variedad debido al pequeño número de casos estudiados.…”
Section: Discusionunclassified
“…Our criteria for grading dyshaemopoiesis were previously published elsewhere (Garcia et al, 1988). Dysplasia of megakaryopoiesis was present in 40 patients (mild in 30: marked in 10) and dysgranulopoiesis in 29 patients (mild in 23; marked in six).…”
mentioning
confidence: 99%
“…The analysis by Sanz et a1 (see accompanying letter) draws on patients that were prediagnosed as clear myelodysplastic syndromes and as such entered in a large study of MDS. The criteria employed for grading dyshaemopoiesis (Garcia et al, 1988) recognize mild dyserythropoiesis if abnormalities are found in > 50% of erythroblasts. This, however, does not cover the full range of AISA, because patients with > 15% ring sideroblasts but < 50% dysplastic red cell precursors would not fulfil their entry criteria.…”
mentioning
confidence: 99%